2022
DOI: 10.1158/0008-5472.can-20-3857
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus Type K Promotes Proliferation and Confers Sensitivity to Antiretroviral Drugs in Merlin-Negative Schwannoma and Meningioma

Abstract: Deficiency of the tumor suppressor Merlin causes development of schwannoma, meningioma, and ependymoma tumors, which can occur spontaneously or in the hereditary disease neurofibromatosis type 2 (NF2). Merlin mutations are also relevant in a variety of other tumors. Surgery and radiotherapy are current first-line treatments; however, tumors frequently recur with limited treatment options. Here, we use human Merlin-negative schwannoma and meningioma primary cells to investigate the involvement of the endogenous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Abacavir has also been suggested to reduce proliferation and induce differentiation in malignant medulloblastoma ( 65 , 66 ). Similarly, Maze et al demonstrated that HIV protease inhibitors reduced proliferation of HERV-K + schwannomas, and meningiomas by eliminating ERK1/2 tumorigenic pathways ( 67 ). Given their favorable pharmacokinetic profile and their specificity for HERV-K, antiretroviral therapeutics may be ideal candidates for cancer drug repositioning.…”
Section: Discussionmentioning
confidence: 99%
“…Abacavir has also been suggested to reduce proliferation and induce differentiation in malignant medulloblastoma ( 65 , 66 ). Similarly, Maze et al demonstrated that HIV protease inhibitors reduced proliferation of HERV-K + schwannomas, and meningiomas by eliminating ERK1/2 tumorigenic pathways ( 67 ). Given their favorable pharmacokinetic profile and their specificity for HERV-K, antiretroviral therapeutics may be ideal candidates for cancer drug repositioning.…”
Section: Discussionmentioning
confidence: 99%
“…Reduce proliferation of schwannoma and meningioma cells, through inhibition of HERV-K PR [31] The integrase inhibitor DTG Inhibit the proliferation of cancer cells, through repression of HERV-K expression [32] The integrase inhibitor Raltegravir Block HERV-K infection and production [26] The inhibitor of MEK, PD98059 or CDK4, 219476…”
Section: Small Molecule Compoundsmentioning
confidence: 99%
“…These microvesicles were reported to carry the ability of horizontal gene transfer between cancer cells, potentially leading to increased levels of HERV proteins in neighboring cells [ 266 ]. HERV-K (HML-2) Env expression has been reported to be upregulated in human Merlin-negative schwannoma and in all meningioma grades via the CRL4 (DCAF1) and YAP/TEAD pathway [ 267 ]. In addition, C-MYC was shown to bind to the HERV-K (HML-2) LTR and lead to env expression, which in turn can be inhibited by SMARCB1 binding free C-MYC [ 268 ].…”
Section: Hervs In Nervous System Cancers—the Wicked Side Of Herv-wmentioning
confidence: 99%
“…Biallelic SMARCB1 is characteristic of atypical Teratoid Rhabdoid Tumor (AT/RT), a rare pediatric central nervous system cancer [ 268 ]. HERV-K (HML-2) Env in turn increases JUN and pERK4/2 when overexpressed in Schwann cells [ 267 ], while retroviral protease inhibitors ritonavir, atazanavir, and lopinavir reduced proliferation of schwannoma and grade I meningioma cells [ 267 ]. Furthermore, ERVW-1 ε and ERVFRD-1 ε were demonstrated to bind to mitochondria of chemo-resistant U87RETO glioblastoma cells.…”
Section: Hervs In Nervous System Cancers—the Wicked Side Of Herv-wmentioning
confidence: 99%